PENGARUH UKURAN PERUSAHAAN, AUDIT CLIENT TENURE , OPINION SHOPPING DAN KONDISI KEUANGAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING-CONCERN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2011-2015 ) - Wulansari Hartono (Universitas Islam Malang, 2017)
The aim of this reserach is to know the effect of financial enterprise condition, standard of enterprise, opinion shopping and audit client tenure toward the opinion reception of audit going concern. The population of this research is manufacturing enterprise that listed in Indonesia Stock Exchange 2011-2015. Sample of this research consists of 76 manufacturing enterprise, 15 enterprise of opinion audit going concern, 512 enterprise of audit client tenure, 280 enterprise of opinion shopping, 118 enterprise of financial condition. Design of this research use secondary data that gotten from the financial manufacturing enterprise statement at www.idx.co.id. The statistic method to test the hypothesis is regression logistic with enter method and significance of 5% level. The result of this research shows standard of enterprise, variability stock, ratio of stock revolution, variability of cost of goods sold do not give significant influence to the stock of accountant method while gross profit margin significantly influence to the stock of accountant method.